The impact of speculation on the pricing of companies listed on the Warsaw Stock Exchange in light of the ICAPM - Urbański, Stanisław (Managerial Economics, 2015)
Research carried out over recent years shows that speculative stock are the reason for inconsistent pricing of stock with the classic CAPM. The present work is an attempt to explain the impact of speculative stock on pricing in light of the ICAPM. The study is conducted using stocks quoted on the Warsaw Stock Exchange (WSE) in 1995–2012. The systematic risk and risk prices components are simulated by two chosen multifactor applications, with different procedures of portfolio construction. The investigated stocks are classified into quaintile portfolios according to established procedures. It has been assumed that both speculative stocks and improper algorithm for the test portfolios sorting contribute to inconsistent stock pricing in light of the ICAPM. As a result, tests are carried out in three modes. All WSE stocks are analyzed in mode 1. In modes 2 and 3 speculative stocks are excluded from the study. The analysis indicate that the results are in line with the extended conjectures.